LITERATURE STUDY OF RECIPROCAL TEACHING LEARNING MODELS BASED ON PALINSCAR AND BROWN THEORY IN IMPROVING STUDENTS SCIENCE LEARNING OUTCOMES IN ELEMENTARY SCHOOLS - Widji Lestari; Fitria Wulandari (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2020)
Abstract: The purpose of this study was to determine and understand the implementation of the reciprocal teaching learning model of students' learning outcomes of natural science (IPA). This research uses library research or what is usually called (library research). Sources of data in this study are primary data sources (Aris Shoimin's book 2014) and secondary data taken from journals that support the research. The approach in this research is literature study which is an activity to look for theoretical references that are relevant to the research. The data collection techniques used were library techniques and documentation techniques. Meanwhile, the analysis technique used is text and discourse analysis. The steps in the learning model developed by Palinscar and Brown have 5 steps. The results of this study indicate that the reciprocal teaching learning model is very influential on student learning outcomes. Reciprocal learning model; teaching improves students' science learning outcomes.